PWWP2A binds distinct chromatin moieties and interacts with an MTA1-specific core NuRD complex. Issue 1 (December 2018) - Link, Stephanie; Spitzer, Ramona; Sana, Maryam; Torrado, Mario; Völker-Albert, Moritz; Keilhauer, Eva; Burgold, Thomas; Pünzeler, Sebastian; Low, Jason; Lindström, Ida; Nist, Andrea; Regnard, Catherine; et al.
Abstract Chromatin structure and function is regulated by reader proteins recognizing histone modifications and/or histone variants. We recently identified that PWWP2A tightly binds to H2A.Z-containing nucleosomes and is involved in mitotic progression and cranial–facial development. Here, using in vitro assays, we show that distinct domains of PWWP2A mediate binding to free linker DNA as well as H3K36me3 nucleosomes. In vivo, PWWP2A strongly recognizes H2A.Z-containing regulatory regions and weakly binds H3K36me3-containing gene bodies. Further, PWWP2A binds to an MTA1-specific subcomplex of the NuRD complex (M1HR), which consists solely of MTA1, HDAC1, and RBBP4/7, and excludes CHD, GATAD2 and MBD proteins. Depletion of PWWP2A leads to an increase of acetylation levels on H3K27 as well as H2A.Z, presumably by impaired chromatin recruitment of M1HR. Thus, this study identifies PWWP2A as a complex chromatin-binding protein that serves to direct the deacetylase complex M1HR to H2A.Z-containing chromatin, thereby promoting changes in histone acetylation levels. PWWP2A is a chromatin-binding transcriptional regulator that mediates mitosis-progression. Here, the authors provide evidence that PWWP2A directly interacts with H2A.Z nucleosomes, DNA and H3K36me3, binds to an MTA1-specific subcomplex of the NuRD complex (M1HR) and promotes changes to histone acetylation.